(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This research explores the role of ecotourism as a strategy to promote sustainable waste management in eco-friendly tourist destinations in Lhokseumawe City, Aceh. The area faces growing waste challenges, particularly at tourist sites, which negatively impact the natural landscape and reduce visitor attraction. The study employs a case study approach, focusing on tourist locations that have implemented ecotourism practices, such as community-based waste management and eco-friendly technologies. Data were gathered through in-depth interviews with key stakeholders, including travel agents, local government representatives, and community residents, as well as direct observations of the waste management systems. Surveys were conducted to gather opinions from tourists, local residents, and businesses on the effectiveness and support for sustainable waste management initiatives. The analysis reveals that while ecotourism practices have been adopted, waste management effectiveness has not significantly improved. The limited implementation of ecotourism principles at some destinations has led to difficulties in maintaining cleanliness, attracting eco-conscious visitors, and fostering collaboration between local communities and the government. Though tourists and local communities generally support ecotourism-based waste management initiatives, many still view waste management as a government responsibility. Based on these findings, the study suggests policy recommendations to strengthen collaboration between local governments, tourism operators, and communities in supporting ecotourism. This research provides valuable insights into sustainable waste management and can serve as a guide for policymakers and tourism practitioners aiming to improve environmental quality through ecotourism strategies.